miR393 Is Required for Production of Proper Auxin Signalling Outputs - Windels, David; Bielewicz, Dawid; Ebneter, Miryam; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia; Vazquez, Franck (PloS one, 2014)
Auxins are crucial for plant growth and development. Auxin signalling primarily depends on four partially redundant F-box proteins of the TIR1/AFB2 Auxin Receptor (TAAR) clade to trigger the degradation of AUX/IAA transcriptional repressors. Auxin signalling is a balanced system which involves complex feedback regulations. miR393 regulation of TAAR genes is important for different developmental programs and for responses to environment. However, so far, the relevance of the two MIR393 genes for Arabidopsis leaf development and their significance for auxin signalling homeostasis have not been evaluated. First, our analyses of mir393a-1 and mir393b-1 mutants and of mir393ab double mutant show that the two genes have only partially redundant functions for leaf development. Expression analyses of typical auxin-induced reporter genes have shown that the loss of miR393 lead to several unanticipated changes in auxin signalling. The expression of DR5pro:GUS is decreased, the expression of primary AUX/IAA auxin-responsive genes is slightly increased and the degradation of the AXR3-NT:GUS reporter protein is delayed in mir393ab mutants. Additional analyses using synthetic auxin and auxin antagonists indicated that miR393 deficient mutants have higher levels of endogenous AUX/IAA proteins, which in turn create a competition for degradation. We propose that the counter-intuitive changes in the expression of AUX/IAA genes and in the accumulation of AUX/IAA proteins are explained by the intrinsic nature of AUX/IAA genes which are feedback regulated by the AUX/IAA proteins which they produce. Altogether our experiments provide an additional highlight of the complexity of auxin signaling homeostasis and show that miR393 is an important component of this homeostasis.